Ð¢ÐµÑ€Ð¼Ð¾Ñ€ÐµÐ³ÑƒÐ»ÑÑ†Ð¸Ñ, ÑÐ¾Ð½ Ð¸ Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð½Ñ‹Ðµ Ð²Ð¾Ð·Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ñ - Ventskovska, O. A.; Shylo, O. V.; Babiychuk, G. O. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
Changes in body temperature, occurring during sleep-wake cycle and sensitivity of sleep to changes of ambient temperature led to the idea that there is an interrelation between sleep regulation and thermoregulation. Numerous studies have shown that sleep is largely influenced by ambient temperature and is sensitive to the intensity, duration and mode of temperature effects. Another reason for the interrelation between sleep regulation and thermoregulation is the fact that hypothalamus, especially the medial preoptic area is involved in sleep regulation and regulation of body temperature.